Coexistence of Darcy and non-Darcy flows in deep limestone aquifers: insights from multi-scale imaging and pore-scale simulation - Wenju Cheng; Chao Niu; Huiyong Yin; Lele Xiao; Qiang Sun; Chengwei Zhang; Songsong Cheng; Dabao Zeng (Journal of Hydrology, 2026)

Temporal variation in secondary metabolites and antioxidant activity during the biotransformation of American ginseng by Monascus purpureus MN 001: Molecular docking analysis of β-glucosidase-mediated ginsenoside hydrolysis - Li Zhang; Zirui Liu; Boyuan Zhang; Miaomiao Yang; Xueling Zhao; Siliang Lyu; Jiahao Bai; Siyuan Bai; Na Liu; Zhongke Sun; Peng Li; Chengwei Li; et al. (Food Bioscience, 2026)

Multi-omics analyses reveal BPA accelerates glioma progression via cell cycle dysregulation - Shimin Lin; Yan Wei; Yuze Wang; Guidong Zhu; Diange Zhang; Feihu Zhao; Chi Zhang; Chengwei Wang; Zhongzheng Sun (Environmental Pollution, 2026)

Urea–NaHCO3 co-activated biochar enhances biohydrogen production via microbial community restructuring and metabolic pathway redirection - Tao Sheng; Jiaxing Meng; Chengwei Song; Changxing Yu; Caiyu Sun; Linlin Huang; Lixin Li; Chunxue Yang; Zhiwei Song (Environmental Research, 2026)

Corrigendum to “Evolution of pyraclostrobin resistance in Botrytis cinerea from Xinxiang City of China and its targeted management via RNA interference” [Pesticide Biochemistry and Physiology 221 (2026) 107105] - Feng Zhou; Haichuan Su; Huifang Jia; Tiancheng Liu; Ziyang Li; Luxun Liu; Yanfen Wang; Weiguo Li; Zhongke Sun; Chengwei Li; Runqiang Liu (Pesticide Biochemistry and Physiology, 2026)

Social media as a sensor: unraveling nonlinear drivers of perceived thermal comfort in Shanghai - Hongping Sun; Chengwei Li; Kangning Huang; Ying Li; ChengHe Guan (Landscape and Urban Planning, 2026)

Identification of Fertility and Internal Genetic Uniformity in Monogerm Sugar Beet Hybrid Combinations - Chengwei Zhang; Rui Gao; Gaofei Lü; Zedong Wu; Linlin Sun (Sugar Tech, 2026)

Evolution of pyraclostrobin resistance in Botrytis cinerea from Xinxiang City of China and its targeted management via RNA interference - Feng Zhou; Haichuan Su; Huifang Jia; Tiancheng Liu; Ziyang Li; Luxun Liu; Yanfen Wang; Weiguo Li; Zhongke Sun; Chengwei Li; Runqiang Liu (Pesticide Biochemistry and Physiology, 2026)

Engineered carbon–biofilm interfaces enable a high-stability single-strain bioanode for real-time BOD monitoring in complex wastewaters - Yingkun Zhang; Hao Zi; Letian Xu; Shaojie Yang; Yi Chen; Chengwei Sun; Young-Chae Song; Qing Feng; Xinjian Zhang (Journal of Environmental Chemical Engineering, 2026)

Microbial community restructuring under crop rotation: A sustainable strategy to counteract potato monoculture-induced soil degradation in arid ecosystems - Zhitao Li; Jinyong Zhu; Tianbin Shi; Chengwei Gao; Xiaoqiang Qiu; Minmin Bao; Yuanming Li; Zhenzhen Bi; Panfeng Yao; Chao Sun; Huaijun Si; Yuhui Liu; et al. (Agriculture, Ecosystems & Environment, 2026)

Elucidating the Effect of Perilla frutescens Extracts with Various Solvents Treatment on the Physicochemical Properties and Flavor Characteristics of Grass Carp Cubes During Cold Storage - Hao Wang; Chengwei Yu; Yanan Sun; Mengke Tian; Bizhen Zhong; Bin Peng; Mingming Hu; Jinlin Li; Zongcai Tu (Journal of Aquatic Food Product Technology, 2026)

Toward clean production of power batteries: An electrode burr detection method fusing line laser scanning and enhanced PointNet++ - Yuedong Sun; Yue Niu; Tianxin Chen; Junjie Chen; Chengwei Hu; Fei Chen; Zihan Zhou; Dawei Li; Yinhua Liu; Guoxin Yu; Yuejiu Zheng (Journal of Cleaner Production, 2026)

Paste-like conductive composites through silver-anchored liquid metal networks with high thermal conductivity and electromagnetic shielding - Chengwei Jiang; Yiqi Xu; Chunfang Zi; Mengwei Tao; Quanshou Feng; Changxiang Hao; Ziyan Yu; Sijin Li; Fangyuan Sun; Haibo Wu; Yuanxin Yan; Liyang Wang; et al. (Chemical Engineering Journal, 2026)

Consolidated bio-saccharification (CBS) enhanced hydrogen production via bioaugmentation to eliminate cellobiose inhibition: Investigation on hydrogen production performance and microbial community - Sheng Tao; Song Chengwei; Liu Qianchi; Song Zhiwei; Yang Chunxue; Sun Caiyu; Li Lixin; Huang Linlin; Wang Miao (Biocatalysis and Agricultural Biotechnology, 2026)

Electric field-driven methanogenesis from low-rank coal: Deciphering synergistic role of direct interspecies electron transfer and conventional microbial pathways - Qing Feng; Chengwei Sun; Yong Zhao; Shaojie Yang; Hao Zi; Yingkun Zhang; Hongda Pan; Xinjian Zhang (Bioresource Technology, 2026)

Black phosphorene fast ion transport channel for asymmetric polymer solid-state lithium metal batteries - Zipeng Sun; Hao Feng; Zhipeng Yin; Jinhao Li; Jianwei Wang; Kai He; Kaijie Miao; Yaoxin Li; Shilin Chen; Chengwei Ma; Jiangqi Zhou; Chunli Li (Chemical Engineering Journal, 2025)

2D ultrathin sheet-like SiO2 embedded reduced graphene oxide anodes for improved lithium kinetics and low-temperature storage - Xiaoxu Lai; Zifang Chen; Chengwei Chen; Chi Chen; Dan Sun (Chemical Engineering Journal, 2025)

Harnessing oxygen-enhanced bioelectrochemical systems (O-BES) and low-voltage stimulation for ultra-high-rate wastewater treatment - Xiaoxiang Li; Qing Feng; Shuping Li; Shaojie Yang; Chengwei Sun; Xinjian Zhang; Yinian Zhou (Chemical Engineering Journal, 2025)

Study on Microscopic Characteristics of Water Absorption and Degradation Mechanisms in Dolomite - Fukun Shi; Xiaoming Sun; Linsen He; Zhigang Tao; Yong Zhang; Chengyu Miao; Chengwei Zhao (Rock Mechanics and Rock Engineering, 2025)

Deep learning-based inversion of stress curves and crack quantification in NPR anchored rock masses - Li Cui; Wenfeng Ren; Chengyu Miao; Yong Zhang; Chengwei Zhao; Sheng-tian Zhai; Ran Hai; Jianjun Ma; Xiaoming Sun (Journal of Mountain Science, 2025)

Micro‐Faunal and Edaphic Controls on Microbial Carbon Cycling Across Primary and Secondary Successional Trajectories - Lei Du; Roland Bol; Chengwei Tu; Xiaolei Sun; Ruyi Luo; Qinghua Liu; Lin Luo; Juan Zhan; Chunying Yin; Biao Zhu; Xueyong Pang; Nicolas Fanin (Global Change Biology, 2025)
The accumulation of microbial‐derived organic carbon in soils during long‐term vegetation succession represents a key pathway for long‐term soil carbon stabilization. Yet, the role of soil microfauna in regulating microbial carbon dynamics remains poorly understood, particularly across divergent successional trajectories (primary vs. secondary successional gradients). We investigated nematode‐microbe interactions influencing carbon dynamics in primary (glacial retreat) and secondary (post‐disturbance) successional chronosequence on the eastern Qinghai‐Tibet Plateau, to identify context‐dependent mechanisms underpinning soil carbon formation and dynamics. Both successional types displayed an ‘S‐shaped’ trajectory of carbon dynamics, initially rising from early to intermediate stages, declining subsequently, then increasing again in late stages, with microbial necromass (quantified by amino sugars) dominating the carbon pool, especially in later stages. In primary succession, characterized by nutrient limitation and slower soil development, nematode‐mediated shifts in microbial community composition and functional gene expression, particularly reductions in growth‐related and decomposition genes, enhanced microbial turnover and necromass accumulation. In contrast, in phosphorus‐limited soils of secondary succession, where nutrient availability and disturbance history play a larger role, declining omnivorous nematodes modulated microbial gene expression to enhance carbon fixation and constrain decomposition under phosphorus‐rich conditions. Soil pH consistently acted as the primary abiotic factor influencing microbial communities across both successional sequences, explaining up to 29% of variation in microbial gene profiles. These findings position microbial necromass accumulation as a central pathway for carbon sequestration and identify nematodes as context‐dependent regulators of microbial carbon processing. Our study underscores the need to integrate both soil microbial and faunal dynamics, along with key physicochemical properties, into ecosystem models to improve predictions of carbon‐climate feedbacks across successional landscapes.

Environmental and economic evaluation of a prefabricated 3D-printed structural units using recycled aggregates from construction and demolition waste: A case study in China - Yufei Wang; Junbo Sun; Xiangyu Wang; Bo Huang; Shuyuan Xu; Jiajie Shang; Shengping Li; Chengwei Song; Dong Wang (Energy and Buildings, 2025)

Enhancing soil ecological stoichiometry and orchard yield through ground cover management: A meta-analysis across China - Weiting Ding; Huizhou Gao; Zhidong Qi; Liangjie Sun; Chengwei Zheng; Jinsong Huang; Vilim Filipović; Hailong He (Agriculture, Ecosystems & Environment, 2025)

The response mechanisms of kelp Macrocystis pyrifera holobiont to elevated temperature and CO2 concentration - Tianle Xi; Yajing Liu; Xiaowen Zhang; Shanshan Ge; Yitao Wang; Ke Sun; Xiao Fan; Dong Xu; Pengyan Zhang; Chengwei Liang; Naihao Ye (Journal of Applied Phycology, 2025)

Evaluation of extraction-oxidation synergistic remediation of contaminated dredged sediment and plant suitability effects - Wenchao Yang; Jize Liu; Yuanshu Sun; Zhaowei Wang; Chengwei Han; Jianbo Han (Frontiers in Marine Science, 2025)
Generally, marine dredged sediments often exhibit co-pollution with heavy metals and petroleum hydrocarbons. This work investigates the extraction-oxidation synergistic remediation treatment of heavy metals (Cu and Pb) and total petroleum hydrocarbon (TPH) in the contaminated dredged sediments. The leachability of heavy metals, the oxidation of TPH, the physicochemical properties of the treated sediment, and the fertility of the treated sediment for barley growth are compared among different combinations of extractants [ethylene diamine tetraacetic acid (EDTA), citric acid (CA) and ferric chloride (FeCl 3 )] and oxidant [potassium persulfate (K 2 S 2 O 8 )]. The results show that the extraction-oxidation synergistic remediation treatment significantly reduces the Cu and Pb contents. The total removal performances of heavy metals and TPH in the contaminated dredged sediments by each co-remediation treatment group are FeCl 3 +Ox > EDTA-Ox > CA-Ox. Specifically, FeCl 3 +Ox and EDTA-Ox achieve the highest removal rates of 91.10% and 96.95% for Cu and Pb, respectively. The extractant affects the activation of K 2 S 2 O 8 by transition metals, enhancing the removal efficiency of TPH. The EDTA-Ox treatment group demonstrates the optimal treatment efficiency (37.42%) for TPH in the dredged sediment in 30 min. In the barley planting experiment, both shoot and root germinations in the EDTA-Ox treatment group reach their maximum values of 100% and 90%, respectively. Additionally, the CA-Ox treatment group exhibits maximal shoot and root lengths of 11.6 cm and 12.1 cm, respectively. The stress caused by salinity on seeds is also mitigated by the treatment. This study can provide technical support for the beneficial use of the dredged sediment.

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Insights into the dynamics of biochemical profile and relative gene expression of cucumber fruits associated with Fusarium spoilage - Muhammad Imran; Hanan A. Khalifa; Zhongke Sun; Muhammad Saqib Bilal; Mohamed Hassan Abd El-Wahed; Kamal A. M. Abo-Elyousr; Esmat F. Ali; Chengwei Li (Journal of Plant Diseases and Protection, 2025)

Water-Soluble Ginseng Oligosaccharides Prevent Scopolamine-Induced Cholinergic Dysfunction and Inflammatory Cytokine Overexpression - Ting Zeng; Chengwei Zhang; Lili Sun; Haiyan Xu (Cell Biochemistry and Biophysics, 2025)

Ground cover management enhances soil extracellular enzyme activities across Chinese orchards - Weiting Ding; Liangjie Sun; Mengyang Wang; Zhidong Qi; Shaohua Wang; Chengwei Zheng; Francis Zvomuya; Hailong He (Journal of Environmental Management, 2024)

Nanoencapsulation enhances the antimicrobial and antioxidant stability of cyclic lipopeptides for controlling Fusarium graminearum - Yanjie Yi; Youtian Shan; Pengyu Luan; Zhongke Sun; Xingquan Wu; Zhiwen Ning; Zhengkun Chen; Yunxiang Zhang; Shuyun Zhao; Chengwei Li (Food Microbiology, 2024)

Photochromic and electrochromic dual-responsive devices: Integration of TiO2-Prussian blue composites and novel extended viologen - Fangyuan Sun; Haibo Wu; Chengwei Jiang; Yonghao Chen; Yanan He; Shiqi Zu; Fengyu Su; Yanqing Tian; Yan Jun Liu (Chemical Engineering Journal, 2024)

Heterogenous impact of background meteorological factors on the cooling effect of two types of typical urban parks: Evidence from Shanghai, China - Xiaolei Geng; Dou Zhang; Wei Sun; Yuan Yuan; Chengwei Li; Zhaowu Yu (Building and Environment, 2024)

Relevance of genetic causes and environmental adaptation of Cronobacter spp. isolated from infant and follow-up formula production factories and retailed products in China: A 7-year period of continuous surveillance based on genome-wide analysis - Wei Tong; Dajin Yang; Shaofu Qiu; Sai Tian; Zehong Ye; Shuran Yang; Lin Yan; Weiwei Li; Ning Li; Xiaoyan Pei; Zhongqing Sun; Chengwei Liu; et al. (Science of The Total Environment, 2024)

Integration of carbon microsheets and helical carbon nanocoils for efficient microwave absorption - Chen Sun; Hao Zhang; Xueqing Zuo; Yuchen Jiang; Yifeng Zhang; Chengwei Li; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2024)

Sodium alginate improves phytase stability and enhances soil phosphorous utilization - Zhongke Sun; Xianyang Feng; Yini Shi; Chengwei Li (Biocatalysis and Agricultural Biotechnology, 2024)

One stone two birds: Endophytes alleviating trace elements accumulation and suppressing soilborne pathogen by stimulating plant growth, photosynthetic potential and defense related gene expression - Muhammad Imran; Zhongke Sun; Kamal A.M Abo-Elyousr; Haider Ali; Munirah F. Aldayel; Chengwei Li (Journal of Hazardous Materials, 2024)

Antifungal efficacy of Bacillus amyloliquefaciens ZK-9 against Fusarium graminearum and analysis of the potential mechanism of its lipopeptides - Yanjie Yi; Pengyu Luan; Minghao Fan; Xingquan Wu; Zhongke Sun; Zijun Shang; Yuzhen Yang; Chengwei Li (International Journal of Food Microbiology, 2024)

Ultra-Flexible microwave absorber of PEDOT:PSS/Melamine composite film with wide tunable frequency controlled by Self-Strain sensing - Xueqing Zuo; Cao Zhou; Tingkang Yuan; Ningxuan Wen; Chen Sun; Hao Zhang; Yifeng Zhang; Jie Tian; Chengwei Li; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2024)

Self-adaptive reconstruction of Zn (0 0 2) crystal plane for highly reversible Zn anodes - Pengju Li; Jisong Hu; Song Yang; Chengwei Wang; Yi Tan; Bing Sun; Cunyuan Pei; Dongmei Zhang; Shibing Ni (Chemical Engineering Journal, 2024)

Failure mechanism and safety control technology of a composite strata roadway in deep and soft rock masses: a case study - Chengwei Zhao; Hui Zhou; Xiaoming Sun; Yong Zhang; Chengyu Miao; Jian Wang (Journal of Mountain Science, 2024)

Hierarchical molecular sieve-based Ce-Ru oxide for enhanced catalytic oxidation of chlorobenzene: Insight into the synergistic effect of Ce and Ru, the role of molecular sieve - Chengwei Yu; Jia-nan Gu; Yixin Xue; Mingming Guo; Kan Li; Jinping Jia; Tonghua Sun (Process Safety and Environmental Protection, 2024)

Non-destructively incorporating ceria in Nafion membrane as hydroxyl radical scavenging agent for long-term PEMFC application - Guodong Xu; Anqi Ke; Feng Ji; Yuxin Liu; Zhiyuan Zhao; Rongguan Lv; Bing Huang; Jing Li; Chengwei Deng; Yuzhen Sun; Weiwei Cai (Fuel, 2024)

Rational synthesis of 1,3,4-thiadiazole based ESIPT-fluorescent probe for detection of Cu2+ and H2S in herbs, wine and fruits - Yu Sun; Jie Mu; Yongchen Wang; Chengwei Lü; Li-Wei Zou (Analytica Chimica Acta, 2024)

Hierarchical processing enabled by 2D ferroelectric semiconductor transistor for low-power and high-efficiency AI vision system - Guangcheng Wu; Li Xiang; Wenqiang Wang; Chengdong Yao; Zeyi Yan; Cheng Zhang; Jiaxin Wu; Yong Liu; Biyuan Zheng; Huawei Liu; Chengwei Hu; Xingxia Sun; et al. (Science Bulletin, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Utilizing Haematococcus pluvialis to simulate animal meat color in high-moisture meat analogues: Texture quality and color stability - Zehua Huang; Ying Liu; Hongzhou An; Zoltan Kovacs; Mehdi Abddollahi; Zhongke Sun; Gaoyang Zhang; Chengwei Li (Food Research International, 2024)

Precise surface reorganization on iron incorporated cobalt oxides/phosphides using plasma technology for alkaline water/seawater electrolytes - Chengwei Sun; Yuan He; Njud S. Alharbi; Muhammad Shaban; Shubin Yang; Changlun Chen (Chemical Engineering Journal, 2023)

Regulation of electrical properties via ferroelectric polarization for high performance Sb2Te3 thermoelectric thin films - Boyu Yang; Yubo Luo; Chengjun Li; Wang Li; Chengwei Sun; Zheng Ma; Yongxin Qian; Xianwei Zeng; Yingchao Wei; Haiqiang Liu; Dan Zhang; Xin Li; et al. (Chemical Engineering Journal, 2023)

SlbHLH152, a bHLH transcription factor positively regulates iron homeostasis in tomato - Xiaoli Li; Haohao Cao; Deshui Yu; Kedong Xu; Yi Zhang; Xinxin Shangguan; Xiaohong Zheng; Zhongzhou Yang; Chaoqiong Li; Xingchen Pan; Yiming Cui; Zhiqing Zhang; et al. (Plant Science, 2023)

Meningeal lymphatics restoration and neurovascular protection synergistically improve traumatic brain injury treatment - Jingquan Lin; Hangxiang Sun; Hongjie Jiang; Rui Xue; Bing Qin; Jianan Lu; Zhoule Zhu; Chengwei Cai; Jiawei Han; Jianmin Zhang; Xiaohua Yu; Junming Zhu (Chemical Engineering Journal, 2023)

Natural siderite derivatives activated peroxydisulfate toward oxidation of organic contaminant: A green soil remediation strategy - Chengwei Zhong; Yinying Jiang; Quanfeng Liu; Xiaoshuang Sun; Jiang Yu (Journal of Environmental Sciences, 2023)

Coastal ecosystem service in response to past and future land use and land cover change dynamics in the Yangtze river estuary - Chengwei Li; Shubo Fang; Xiaolei Geng; Yuan Yuan; Xiaowei Zheng; Dou Zhang; Rongxi Li; Wei Sun; Xiangrong Wang (Journal of Cleaner Production, 2023)

A genome-wide association study reveals that the cytochrome b5 involved in seed reserve mobilization during seed germination in rice - Zhibo Huang; Jifeng Ying; Liling Peng; Shan Sun; Chengwei Huang; Can Li; Zhoufei Wang; Yongqi He (Theoretical and Applied Genetics, 2021)

Optimization analysis of NPR cable support considering bearing structure in the NSF condition of deep shaft based on Daqiang coal mine - Chengwei Zhao; Xiaoming Sun; Yong Zhang; Shangkun Zhang; Jiaxuan Zhang (Arabian Journal of Geosciences, 2021)

Failure mechanism and control technology of large deformation for Muzhailing Tunnel in stratified rock masses - Xiaoming Sun; Chengwei Zhao; Zhigang Tao; Hongwei Kang; Manchao He (Bulletin of Engineering Geology and the Environment, 2021)

Physical model experiment and numerical analysis on innovative gob-side entry retaining with thick and hard roofs - Xiaoming Sun; Chengwei Zhao; Gan Li; Bo Zhang; Junwei Wang; Feng Cai (Arabian Journal of Geosciences, 2020)

Using probiotics for type 2 diabetes mellitus intervention: Advances, questions, and potential - Zhongke Sun; Xuejiao Sun; Juan Li; Zhaoyang Li; Qingwei Hu; Lili Li; Xinqi Hao; Maoping Song; Chengwei Li (Critical Reviews in Food Science and Nutrition, 2020)

Silencing of glycerol-3-phosphate acyltransferase 6 (GPAT6) gene using a newly established virus induced gene silencing (VIGS) system in cucumber alleviates autotoxicity mimicked by cinnamic acid (CA) - Ruifang Bu; Runhao Wang; Qichao Wei; Haiyan Hu; Haili Sun; Puwen Song; Yongang Yu; Qili Liu; Zichao Zheng; Tong Li; Dongxiao Li; Lei Wang; et al. (Plant and Soil, 2019)

Application Research on Gob-Side Entry Retaining Methods in No. 1200 Working Face in Zhongxing Mine - Sun Xiao-ming; Li Gan; Song Peng; Miao Chengyu; Zhao Chengwei; Li Qi; Xia Xing (Geotechnical and Geological Engineering, 2019)

Physical modeling experimental study on failure mechanism of surrounding rock of deep-buried soft tunnel based on digital image correlation technology - Xiaoming Sun; Peng Song; Chengwei Zhao; Yong Zhang; Gan Li; Chengyu Miao (Arabian Journal of Geosciences, 2018)

IAA producing Bacillus altitudinis alleviates iron stress in Triticum aestivum L. seedling by both bioleaching of iron and up-regulation of genes encoding ferritins - Zhongke Sun; Kun Liu; Ju Zhang; Yi Zhang; Kedong Xu; Deshui Yu; Jian Wang; Lizong Hu; Long Chen; Chengwei Li (Plant and Soil, 2017)

TCTP Expression After Rat Spinal Cord Injury: Implications for Astrocyte Proliferation and Migration - Jianbing Ren; Xingxing Mao; Minghao Chen; Weidong Zhang; Yang Liu; Chengwei Duan; Haiyan Zhang; Chi Sun; Weijie Wu; Xinjian Zhu; Jianbing Ge; Weidong Tao; et al. (Journal of Molecular Neuroscience, 2015)

Detection of spotted fever group Rickettsiae in ticks from Zhejiang Province, China - Jimin Sun; Junfen Lin; Zhenyu Gong; Yue Chang; Xiaodong Ye; Shiping Gu; Weilong Pang; Chengwei Wang; Xiaohua Zheng; Juan Hou; Feng Ling; Xuguang Shi; et al. (Experimental and Applied Acarology, 2015)

GASA5, a regulator of flowering time and stem growth in Arabidopsis thaliana - Shengchun Zhang; Chengwei Yang; Jianzong Peng; Shulan Sun; Xiaojing Wang (Plant Molecular Biology, 2009)